Leaving legacies: African American men discuss the impact of their fathers on the development of their own paternal attitudes and behavior. Issue 1 (1st January 2016) - Perry, Armon; Lewis, Susan
ABSTRACT: In recent years there has been an increase in research examining issues related to fathers. Despite these contributions to the literature, studies including primarily African American samples disproportionately feature fathers who are non-resident, low income, or incarcerated. Thus, little is known about African American men from across the social and economic spectrum. To fill this gap, this qualitative analysis features a diverse sample of African American men discussing their relationships with their fathers and influence of those relationships on their own fathering attitudes and behaviors. Findings revealed that most of the participants modeled their fathers' behavior. The findings also revealed that participants described their parenting as attempts to leave their children and communities with a legacy of engaged fathering.